Kajian Literatur Mengenai Pengelolaan Kawasan Hutan dengan Tujuan Khusus sebagai Upaya Konservasi Keanekaragaman Hayati Berdasarkan UU Nomor 41 Tahun 1999 - Iqbal Sabgianto; Maya Robiyanti; Ferdi Saputra; M. Setia Budi; Muhammad Ilham; Muhammad Syafiq; Ika Dwimaya Roza (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
Special Purpose Forest Areas (KHDTK), as regulated in Article 8 of Law Number 41 of 1999 concerning Forestry, are legal instruments that provide additional functions to forest areas without changing their primary functions, and in practice are often directed towards education, research, and biodiversity conservation. This study aims to analyze the extent to which KHDTK management is effective as a biodiversity conservation instrument outside formal conservation areas, and to identify supporting and inhibiting factors for its optimization. The study used a systematic literature review method for national regulations, policy documents, and scientific articles discussing KHDTK management in the 2015–2025 publication period, which were analyzed descriptively and qualitatively using content analysis techniques. The results of the study indicate that KHDTK such as Penggaron (Diponegoro University), Samboja (East Kalimantan), and the Mulawarman University Research and Education Forest (HPPUM) contain significant flora and fauna wealth, but their conservation effectiveness is greatly influenced by the clarity of area boundaries, the intensity of anthropogenic pressures, and the involvement of management institutions and surrounding communities. A gap was also identified between generic regulatory design and the need for adaptive management based on the ecological characteristics of the site. The study concluded that optimizing KHDTK as a conservation instrument requires strengthening collaborative governance, integrating management plans with current biodiversity data, and harmonizing regulatory derivatives following the Job Creation Law. This study provides a conceptual contribution to the development of KHDTK management policies that are more oriented toward conservation outcomes, rather than simply area designation status.